EFFECT OF FISH MEAL WITH DIFFERENT PROTEIN CONTENT ON THE WATER QUALITY PARAMETER OF CATFISH (Mystus nemurus CV) MEDIA IN AQUAPONIC RECIRCULATION SYSTEMS - Dimas Pratama; Mulyadi '; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The objective of the research was to determine the effect of feeding with different protein contents on the quality of water in fish culture catfish media (M. nemurus CV) in a recirculating aquaponics system. The method used in this study is the experimental method using a completely randomized design (CRD) using 1 factor, 4 levels of treatment and 3 replication, the treatment is: P0 (control), P1 (Giving pellets artificial protein content 30%), P2 (Pellets with protein content 35%) and P3 (pellet-made with a protein content of 40%. The results of this study are growth weight (g) cathfish best there is in treatment P2 (feeding with protein content of 35%) The final results of the absolute weight of 3.92 g, with the best water quality parameters, namely: 27,8-28,6oC temperature, pH 6.74 to 6.79, dissolved oxygen 5.21 to 5.26 mg / L, nitrate 4.33 mg / L, orthopospate 0.83 mg / L and ammonia 0.0055 mg / L. The length of vegetable mustard at the end of the study is of 5.72 cm.Keyword : Mystus nemurus CV, Aquaponics, Water Quality Parameters